The effect of the Pharmaiod preparation in the virus elimination of pear plants using the thermotherapy method - M. T. Upadyshev (Аграрная наука Евро-Северо-Востока)
Currently, the main methods of virus elimination of fruit crops are dry-air thermotherapy, meristem culture and chemotherapy. The use of a complex of physical and chemical methods makes it possible to increase the efficiency of virus elimination. Improving the methods of recovery must be carried out in relation to certain types of viruses, the biological characteristics of the crop and variety. The purpose of the research is to study the effect of the Pharmaiod preparation on biometric, physiological parameters and the release of harmful viruses-free pear plants in the process of dry-air thermotherapy. Improvement of pear plants of varieties Letnyaya Zabava, Zolotoy Vityaz, hybrids R-11-9, R-10-3 and R-2-4 from harmful latent viruses of Apple stem grooving virus (ASGV), Apple stem pitting virus (ASPV), Apple chlorotic leaf spot virus (ACLSV), Apple mosaic virus (ApMV) were carried out in 2020-2021 at the temperature of 38 °C for 3 months using a thermal chamber designed by the Federal Horticultural Research Centеr for Breeding, Agrotechnology and Nursery. Biometric parameters in pear plants depended on varietal characteristics, the duration of therapy and the concentration of the Pharmaiod preparation. In most of the varieties and forms studied, after 3 months of thermotherapy, the Pharmaiod preparation at a concentration of 1 ml/l contributed to an increase in the length of 1 shoot of pear plants by 1.4-3.1 times compared with the control. Under the conditions of a thermal chamber, according to a set of indicators, pear hybrids R-11-9 and R-10-3 were characterized by the highest heat resistance; medium heat resistance was shown by Letnyaya Zabava and Zolotoy Vityaz varieties; low – by R-2-4 hybrid. Higher heat-resistant varieties and forms were characterized by a more restrained growth of shoots in length compared to lower heat-resistant ones. An average negative significant correlation at the 5% significance level was established between the water content in the leaves and the length of 1 shoot (r = -0.52). The yield of virus-free pear plants depended on the type of virus. The yield of pear plants free from 4 major harmful viruses as a result of dry-air thermotherapy without the use of the Pharmaiod preparation was 50 %, with the use of the drug it was 60 %.